Synthesis of MUC1-derived glycopeptide bearing a novel triazole STn analog. (December 2020) - Marchiori, Marcelo F.; Bortot, Leandro O.; Carvalho, Ivone; Campo, Vanessa L.
Abstract: The synthesis of MUC1 glycopeptides bearing modified tumor-associated carbohydrate antigens (TACAs) represents an effective strategy to develop potential antitumor vaccines that trigger strong immune response. In this context, we present herein the multistep synthesis of the triazole glycosyl amino acid Neu5Ac-α/β2-triazole-6-βGalNAc-ThrOH 1 as STn antigen analog, along with its assembly on the corresponding MUC1 peptide to give NAcProAsp [Neu5Acα/β2-triazole-6-βGalNAc]ThrArgProGlyOH 2 . Despite interacting differently with SM3 monoclonal antibody, as shown by molecular dynamic simulations, this unnatural triazole glycopeptide may represent a promising candidate for cancer immunotherapy. Graphical abstract: Image 1 Highlights: Synthetic unnatural triazole MUC1-glycopeptide may represent a promising candidate for cancer immunotherapy. Novel triazole glycosyl amino acid Neu5Ac-α/β2-triazole-6-βGalNAc-ThrOH was synthesized as analog of STn antigen by CuAAC reaction. The MUC1-glycopeptide NAcProAsp[Neu5Acα/β2-triazole-6-βGalNAc]ThrArgProGlyOH was successfully obtained by solid-phase assembly